2005
DOI: 10.1007/s10802-005-3563-7
|View full text |Cite
|
Sign up to set email alerts
|

Peer Influence in Children and Adolescents: Crossing the Bridge from Developmental to Intervention Science

Abstract: Considerable evidence supports the hypothesis that peer relationships influence the growth of problem behavior in youth. Developmental research consistently documents the high levels of covariation between peer and youth deviance, even controlling for selection effects. Ironically, the most common public interventions for deviant youth involve segregation from mainstream peers and aggregation into settings with other deviant youth. Developmental research on peer influence suggests that desired positive effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
196
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(221 citation statements)
references
References 61 publications
10
196
0
7
Order By: Relevance
“…It may be that greater perceived peer acceptance by youths who drink and drive refl ects an accurate assessment of their peers' attitudes and behaviors. Adolescent peer groups show increasing levels of similarity in externalizing and risk-taking behaviors over time (Gifford-Smith et al, 2005). This interpretation is also supported by evidence: Changes in normative beliefs became more positive not only for those with prior drinking-and-driving experience but also as a function of time, and these changes exhibited an interaction between time and license status.…”
Section: Discussionmentioning
confidence: 68%
“…It may be that greater perceived peer acceptance by youths who drink and drive refl ects an accurate assessment of their peers' attitudes and behaviors. Adolescent peer groups show increasing levels of similarity in externalizing and risk-taking behaviors over time (Gifford-Smith et al, 2005). This interpretation is also supported by evidence: Changes in normative beliefs became more positive not only for those with prior drinking-and-driving experience but also as a function of time, and these changes exhibited an interaction between time and license status.…”
Section: Discussionmentioning
confidence: 68%
“…It was hypothesized that (1) children's sensation seeking, affiliation with deviant peers, and social images, increase over time, (2) children with higher initial levels of sensation seeking, and steeper growth in sensation seeking, will be more likely to be using marijuana in adolescence, (3) initial levels and growth in childhood sensation seeking will predict both initial levels and growth of later deviant peer affiliation and favorability of social images of marijuana users, and (4) these intervening variables were hypothesized to mediate the effect of sensation seeking on marijuana use. Because boys typically have higher levels of sensation seeking than girls (Zuckerman et al, 1978), and deviant peer affiliation may have stronger effects on girls than boys (Andrews, 2005;Gifford-Smith, Dodge, Dishion, & McCord, 2005), gender differences in this model were examined.…”
Section: Introductionmentioning
confidence: 99%
“…In this regards, Weinstein reported that friends and peers important reason in predicting drug use. Many of study's also reported families and friends have a role in the substance abuse; it seems that life skills education can be the usefulness results [18][19][20][21].…”
Section: Discussionmentioning
confidence: 96%